PENGARUH PRAKTIK KERJA INDUSTRI TERHADAP KESIAPAN KERJA SISWA KELAS XI KOMPETENSI KEAHLIAN AKUNTANSI SMK LABOR BINAAN FKIP UR PEKANBARU - Syabrus, Hardisem; ', Nurhasyima; ', Gusnardi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine how the influence of the IndustrialEmployment Practices Work Readiness Skills Competency Class XI student ofAccounting in Vocational Guidance and Counseling Labor Patronage UR Pekanbaru on64 students have completed the criteria Industry Employment Practices in the BusinessWorld or World Industry (DUDI). Data analysis techniques used in this study is asimple linear regression analysis were used to observe the effect of the Industrial WorkPractices Work Readiness Skills Competency Class XI student of Accounting inVocational Guidance and Counseling Labor Patronage UR Pekanbaru. Thequestionnaire results from 54 respondents obtained more than 50% of students statedthat the industry work practices have been very appropriate. As for the Work Readinessindicators obtained their statements that do not conform are indicators of science. Theresults of the simple linear regression analysis obtained by the positive influence of theIndustrial Employment Practices Work Readiness amounted to 21.50%, while 78.50%influenced by other factors. It can be concluded that the results of this study are positiveinfluence between the Industrial Employment Practices Work Readiness significantly.Keywords: Work Practices Industry, Job Readiness